Cluster policy resilience: new challenges for a mature policy. (14th August 2019) - Wilson, James R.
Cluster policy has proved to be an extremely resilient feature of the regional competitiveness policy landscape over 30 years. To examine why cluster policies have become so widespread, this paper makes a clear conceptual distinction between clusters themselves, cluster policies, and cluster policy instruments. This distinction helps to disentangle the cross-over with other policies and provides the foundations for exploring new directions. Three sets of challenges for what is now a mature policy are highlighted: the links between clusters, cluster policies and territorial strategy processes; more effective evaluation of how different policy instruments influence what happens inside clusters; and harnessing the capacity of clusters to respond to social alongside economic challenges.